Teacher’s belief and its implication on integrating CALL - Desy Nur Fakhomah; Abdul Asib; Dewi Rochsantiningsih (Aksara: Jurnal Bahasa dan Sastra, 2020)
These days, the development of science and technology achieved has contributed to the advance in language teaching and learning. Nowadays, language teachers utilize computer and internet with their software and facilities for the purpose of teaching and learning activities in the classrooms. The use of computer assisted language learning (CALL) for language teaching and learning is not only at formal school such as elementary school, high school and university, but it is also used at informal school such as Sanggar Kegiatan Belajar (SKB). Therefore, this study aims to investigate teacher’s belief and its implication on integrating CALL in English class at SKB (Sanggar Kegiatan Belajar). For reaching the aims, a qualitative method is conducted towards the participant who has used CALL for language teaching and learning at SKB. The participant is purposively selected in order to get sufficient data of this research. The questionnaire, interview and classroom observation are used for collecting data. The result of this study shows that the teacher has positive belief towards CALL integration in English teaching and learning process. Besides, the participant also implies the CALL integration by explaining materials through Power Point and You Tube, giving quiz and homework through Google form. Thus, the teacher’s beliefs has implicated in the English teaching and learning at Sanggar Kegiatan Belajar and CALL is useful for English teaching and learning process at Sanggar Kegiatan Belajar. http://dx.doi.org/10.23960/aksara/v21i1.pp57-73